Analisis Laporan Keuangan Sebagai Alat Untuk Mengukur Kinerja Keuangan Pada Raihan Bakery And Cake Shop Jl. Denai No. 181C Medan - Dharma, Budi; Septia, Windy; Lubis, Suci Arifah (Jurnal Manajemen Akuntansi (JUMSI), 2022)
Businesses in the food manufacturing sector are Raihan Bakery and Cake Shop Jl. Denai No. 181 C Medan. Various types of bread are produced by Raihan Bakery Cake Shop Medan which also operates shops where customers can buy the company's goods. The purpose of this research is to find out the analysis of financial statements so far which should be used as a tool to measure financial performance at Raihan Bakery and Cake Shop Jl. Denai No. 181 C Medan. The findings show Raihan Bakery and Cake Shop Jl. Denai No. 181 C Medan that until now to measure the level of success of a business that has only been carried out in a straightforward manner is by looking at the financial reports presented each period. This was actually done after analyzing financial statements using financial ratios because it was reported that liquidity contributed to good performance, solvency and profitability, while activity and expansion were blamed for poor performance levels. By directly looking at the financial reports from Raihan Bakery and Cake Shop, data for field studies was immediately collected. The research was carried out by means of observation, namely through direct observation in a more in-depth and comprehensive manner towards the object of research. Make direct observations of Raihan Bakery and Cake Shop's financial reports and gather important information using the company's financial reports for 2020, 2021 and 2022.